Is it Corporate Governance, Industry, and Profitability Matter on Esg Performance? Evidence from Indonesian Companies - Fajri Adrianto; Mohamad Fany Alfarisi; Filardi Rahmadani (Journal of Social Research, 2023)
This study aims to test and provide empirical evidence regarding the influence of corporate governance (percentage of independent commissioners), industry, and profitability (ROA and retention ratio) on environmental, social, and governance (ESG) performance. This study also uses two control variables: company size and company age. The objects of this study are companies listed on the Indonesia Stock Exchange (IDX) that have complete ESG scores from the Thomson Reuters Eikon database for 2011-2020. The sample companies are 25 companies selected based on the purposive sampling method. Hypothesis testing was carried out using panel data regression analysis with the STATA 14.0 program. The results of the study show that the industry variable, profitability (retention ratio), has a negative and significant effect on ESG performance. For corporate governance variables (independent commissioners), profitability (ROA) has no effect on ESG performance. This study adds value to the existing literature because it provides an overview of the impact of the factors used on ESG performance in companies in Indonesia.